2011
DOI: 10.1111/j.1939-0025.2011.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Who are the fathers in healthy families Arizona? An examination of father data in at‐risk families.

Abstract: Despite substantial research documenting the importance of father-child relations, little is known about fathers in families considered at risk for child abuse, and this lack of information makes adequate targeting of fathers in interventions challenging. This research aims to provide information that will aid interventions in targeting fathers and addressing father-related family issues through: (a) providing descriptive information regarding fathers in families at risk for child abuse, and (b) examining aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
12
0
3
Order By: Relevance
“…Além disso, quanto maior a capacidade do pai para lidar com tarefas fi nanceiras (representada pela renda familiar mensal e pela posse de carros), maior o nível de envolvimento paterno (Shapiro et al, 2011). Em relação à saúde mental do pai, van Ee et al (2013) apontaram a infl uência negativa do estresse pós-traumático sobre a qualidade da relação pai-fi lho.…”
Section: Fatores Que Afetam O Envolvimento Paternounclassified
See 1 more Smart Citation
“…Além disso, quanto maior a capacidade do pai para lidar com tarefas fi nanceiras (representada pela renda familiar mensal e pela posse de carros), maior o nível de envolvimento paterno (Shapiro et al, 2011). Em relação à saúde mental do pai, van Ee et al (2013) apontaram a infl uência negativa do estresse pós-traumático sobre a qualidade da relação pai-fi lho.…”
Section: Fatores Que Afetam O Envolvimento Paternounclassified
“…Pesquisadores observaram que quanto menor o envolvimento paterno ou a satisfação materna com este envolvimento, mais intensos os sintomas de depressão pós-parto materna (Fagan, & Lee, 2010; e maior a percepção de solidão materna (Shapiro et al, 2011). Além disso, Alexander et al (2010) estudaram expectativas sobre o período de amamentação, encontrando que o apoio do pai infl uenciou signifi cativamente na intenção e no posterior envolvimento da mãe na amamentação.…”
Section: Impactos Do Envolvimentounclassified
“…Researchers found that the more limited the father's initial involvement, or the lower the mother's satisfaction with this involvement, the more intense the symptoms of maternal postpartum depression (Fagan, & Lee, 2010;Sé-journé, Beaumé, et al, 2012; and the greater the sense of maternal loneliness (Shapiro et al, 2011). In addition, Alexander et al (2010), found that the father's support signifi cantly infl uenced the mother's intention and subsequent involvement in breastfeeding.…”
Section: Outcomes Of Father Involvement For Thementioning
confidence: 99%
“…Frascarolo et al (2005) reported stronger family alliances when the father was more participative. In a third study, Shapiro et al (2011) found associations between positive father involvement and: (a) better prenatal care during pregnancy, (b) fewer cases of domestic physical violence, and (c) higher family income.…”
Section: Outcomes Of Father Involvement For Thementioning
confidence: 99%
See 1 more Smart Citation